Efektivitas permainan monopoli untuk meningkatkan pengetahuan tentang budaya Sulawesi Selatan pada siswa di Runiah School - Sri Rindayani; Thesa Aulia Pandung Radha; Yusuf Muhammad Nur; Sri Rahayu; Sri Wahyuni Salman; Eva Meizara Puspita Dewi (University of Muhammadiyah Malang, 2022)
Monopoly game is a game specially modified to be used as a learning medium. The use of games as learning media is used to make students interested and happy to learn. The purpose of implementing this monopoly game is to introduce the culture in South Sulawesi to students at Runiah School. The cultural monopoly game was played by 4 fifth-grader at Runiah School. The results obtained from the implementation of the cultural monopoly game show that the cultural monopoly game helps significantly increase students' understanding of culture in South Sulawesi.